Hydrogen peroxide modified sodium hyaluronate / polylysine hydrogel and preparation method thereof

By using sodium hyaluronate peroxide and reacting with polylysine to generate a modified hydrogel, the problems of low oxidation and unsafe oxidant in the prior art are solved, and hydrogel preparation with high bond strength, antibacterial and water-holding ability is achieved.

CN119798713APending Publication Date: 2025-04-11ANHUI POLYTECHNIC UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411938799.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the process of using sodium periodate to oxidize sodium hyaluronate has a low degree of oxidation, requires dialysis purification, and has a long time, and the oxidant is not safe and green enough.

Method used

Hydrogen peroxide is used to modify sodium hyaluronate, and aldehyde groups are formed by oxidizing the hydroxyl group of sodium hyaluronate, and reacting with polylysine to form a hydrogel, thereby improving the adhesion strength and antibacterial ability of the hydrogel.

Benefits of technology

The high bond strength, bacteriostatic and water-holding capacity of the hydrogel is achieved, the preparation process is simplified, the dialysis steps are avoided, and the hydrogen peroxide is used is safer and greener.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798713A_ABST
    Figure CN119798713A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of hydrogen peroxide modified sodium hyaluronate / polylysine hydrogel, which comprises the following steps: heating sodium hyaluronate in ultrapure water until the sodium hyaluronate is completely dissolved to obtain a sodium hyaluronate aqueous solution; slowly dropwise adding a hydrogen peroxide solution into the sodium hyaluronate aqueous solution, and continuously stirring for 10-30 minutes after dropwise adding; adding polylysine powder into the obtained mixed solution, and continuously stirring for 20-30 minutes; spreading the reaction liquid, and drying at 40-60 DEG C to obtain a hydrogel film; soaking the hydrogel film in ultrapure water until the hydrogel film is swelled and balanced; hydroxyl groups of sodium hyaluronate are modified by hydrogen peroxide to generate aldehyde groups, so that oxidized sodium hyaluronate and polylysine are subjected to Schiff base reaction to prepare the hydrogel, and the hydrogel has relatively high bonding strength, has the properties of bacteriostasis, relatively high water holding capacity and the like, and has the potential of being applied as a drug carrier or wound dressing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogels, and particularly relates to a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel and a preparation method thereof. Background Art

[0002] Sodium Hyaluronate (HA) is a non-immunogenic and biodegradable linear anionic acidic polysaccharide that is widely present in the vitreous, skin, umbilical cord and synovial fluid of humans and animals. It has excellent moisturizing properties, biocompatibility and biodegradability, and also has a variety of necessary physiological functions, which are closely related to many physiological activities of the human body such as cell division and signal transduction. It has been used to produce different wound dressings, namely sponges, films, hydrogels and electrospinning membranes. Hydrogen peroxide is used as an oxidant. In industrial use, it can oxidize the hydroxyl group of sodium hyaluronate to generate aldehyde groups. Not only that, low levels of hydrogen peroxide also have an antibacterial effect.

[0003] Polylysine (ε-polylysine, EPL) is a linear polymer formed by connecting multiple lysine molecules through amide bonds between α-amino and carboxyl groups. In biological applications, it has a broad spectrum of antibacterial activity and good biocompatibility. It can interact with biological tissues and will not cause a strong immune response under appropriate circumstances, which provides a basis for its application in drug delivery, tissue engineering, etc.

[0004] As a new type of medical wound dressing, hydrogel has received extensive attention in clinical applications in recent years. Its unique three-dimensional network structure and polymer swelling properties give hydrogel good water absorption and biocompatibility, making it an ideal material for promoting wound healing and inhibiting bacterial growth. The ability to combine sodium hyaluronate and polylysine to prepare hydrogel can further improve the performance and application range of hydrogel.

[0005] Chinese patent CN 118027454 A discloses a cross-linked sodium hyaluronate gel for injection and a preparation method thereof, comprising the following steps: a first step, adding sodium hyaluronate to water, adding sodium periodate, carrying out an oxidation reaction, adding ethanol to terminate the reaction, dialyzing and purifying to obtain aldehyded sodium hyaluronate; a second step, adding aldehyded sodium hyaluronate and polylysine grafted polyethylene glycol to a phosphate buffer, mixing evenly to obtain a gel; a third step, squeezing the gel through a sieve, and sterilizing to obtain an injection.

[0006] In the above patent, sodium periodate is used as an oxidant to oxidize sodium hyaluronate. The oxidation degree of this oxidation reaction is low, and a dialysis purification step is required after the oxidation reaction. The whole process takes a long time. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for preparing a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel. The hydroxyl groups of sodium hyaluronate are modified by hydrogen peroxide to generate aldehyde groups, so that the oxidized sodium hyaluronate and polylysine produce a Schiff base reaction to prepare a hydrogel, which has strong bonding strength, antibacterial properties, strong water holding capacity and the like, and has the potential to be used as a drug carrier or wound dressing.

[0008] The technical solution adopted by the present invention is as follows:

[0009] A method for preparing a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel, the method comprising the following steps:

[0010] (1) heating sodium hyaluronate in ultrapure water until it is completely dissolved to obtain a sodium hyaluronate aqueous solution;

[0011] (2) slowly adding hydrogen peroxide solution to the sodium hyaluronate aqueous solution, and continuing to stir for 10 to 30 minutes after the addition is completed;

[0012] (3) adding polylysine powder to the mixed solution obtained in step (2) and continuing stirring for 20 to 30 minutes;

[0013] (4) spreading the reaction solution obtained in step (3) and drying it at 40 to 60° C. to obtain a hydrogel film;

[0014] (5) Soaking the hydrogel film in ultrapure water until swelling equilibrium is achieved to obtain a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel.

[0015] In step (1), the heating temperature is 40-60°C.

[0016] In step (1), the concentration of the sodium hyaluronate aqueous solution is 5 to 10 g / L.

[0017] The mass ratio of the sodium hyaluronate to polylysine is 1:1.0-4.0.

[0018] The mass ratio of the sodium hyaluronate to hydrogen peroxide is 1:0.018-0.04.

[0019] In step (2), the mass concentration of the hydrogen peroxide solution is 20-30%.

[0020] In step (2), the dropping speed of the hydrogen peroxide solution is 35 to 45 mL / h.

[0021] In step (5), the mass volume ratio of the hydrogel film to ultrapure water is 1 mg: 2-10 mL.

[0022] The present invention also provides a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel prepared by the preparation method, which has strong bonding strength, antibacterial properties, strong water holding capacity and the like, and has the potential to be used as a drug carrier or wound dressing.

[0023] The preparation method of the hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel provided by the present invention comprises the following steps: using hydrogen peroxide to oxidize sodium hyaluronate to generate oxidized sodium hyaluronate, and the oxidized sodium hyaluronate reacts with polylysine to generate an adhesive hydrogel, which has a strong loading capacity for negatively charged drugs and a certain antibacterial ability.

[0024] The hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel provided by the present invention contains a large number of hydrophilic groups such as carboxyl, hydroxyl, and amino groups in the sodium hyaluronate and polylysine structures in its raw materials, and has a strong water-locking ability. Sodium hyaluronate is negatively charged under physiological conditions, because some carboxyl groups in its molecules may be ionized in solution to produce carboxylate ions. Polylysine molecules contain multiple lysine residues, and the primary amine groups of lysine side chains can be protonated under certain conditions to form positively charged ammonium ions, so that the polylysine is positively charged as a whole. Based on the principle of electrostatic attraction, electrostatic interaction can occur between positively charged polylysine and negatively charged sodium hyaluronate, and condensation reaction occurs between the primary amine groups of polylysine and the carboxyl groups of sodium hyaluronate under the specific conditions of hydrogen peroxide oxidation. During the reaction, the carboxyl group loses the hydroxyl group, and the primary amine group loses the hydrogen atom, and the two combine to form an amide bond.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] (1) The present invention proposes for the first time that sodium hyaluronate, hydrogen peroxide and polylysine are the main components of the hydrogel. The hydrogel obtained by Schiff base reaction and hydrogen bonding has better bonding strength and water absorption and retention properties than sodium hyaluronate polylysine hydrogel.

[0027] (2) The present invention uses hydrogen peroxide to oxidize sodium hyaluronate polylysine hydrogel, which can effectively achieve the regulation of hydrogel membrane structure, performance and drug loading type. Sodium hyaluronate reacts with hydrogen peroxide so that its own hydroxyl group is oxidized to generate aldehyde group. By adding polylysine, the aldehyde group reacts with the amino group in the polylysine to produce Schiff base reaction, so that the hydrogel has adhesion and injectable properties.

[0028] (3) The present invention uses sodium hyaluronate / hydrogen peroxide / polylysine to further improve the adhesion performance, water absorption and retention, antioxidant and antibacterial effects of sodium hyaluronate / polylysine hydrogel, thereby expanding its application range.

[0029] (4) The present invention is synthesized and prepared under mild conditions, and the production process is simple. It has low cost, low equipment requirements, and is green and pollution-free, and has great development potential.

[0030] (5) The present invention proposes for the first time to use hydrogen peroxide to oxidize sodium hyaluronate, which is safer and greener than other oxidants. No dialysis is required after the reaction is completed, and the biocompatibility of the hydrogel is better, making it promising for application in the field of drug delivery systems or wound dressings. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The infrared spectra of the hydrogels prepared in Comparative Example 1 and Example 1 and their 3200-1500 cm -1 Infrared peak processing diagram of the band, the solid line represents the fitting curve, and the dotted line is the fitting peak.

[0032] Figure 2 The results of measuring the adhesive strength of the hydrogels prepared in Example 1, Example 2, and Example 3, wherein: b-Example 1, c-Example 2, d-Example 3;

[0033] Figure 3 The water absorption and water retention test results of the hydrogels prepared in Comparative Example 1, Example 1, Example 2, and Example 3, wherein: a-Comparative Example 1, b-Example 1, c-Example 2, d-Example 3;

[0034] Figure 4 The antibacterial test results of the hydrogels prepared in Comparative Example 1, Example 1, Example 2, and Example 3, wherein: a-Comparative Example 1, b-Example 1, c-Example 2, d-Example 3;

[0035] Figure 5 The in vitro degradation test results of the hydrogels prepared in Comparative Example 1, Example 1, Example 2, and Example 3;

[0036] Figure 6 The MO release results of the hydrogels prepared in Comparative Example 1, Example 1, Example 2, and Example 3 are shown. DETAILED DESCRIPTION

[0037] The present invention is described in detail below with reference to the embodiments.

[0038] Example 1

[0039] A method for preparing a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel comprises the following steps:

[0040] (1) dispersing 0.98 g of sodium hyaluronate in 131.6 mL of ultrapure water, stirring at 45° C. and 450 rpm to fully dissolve the sodium hyaluronate, to obtain a sodium hyaluronate aqueous solution;

[0041] (2) slowly adding 8.4 mL of a 30% hydrogen peroxide solution to the sodium hyaluronate aqueous solution at a rate of 40 mL / h, and continuing stirring at 45° C. and 500 rpm for 10 min;

[0042] (3) Add 1.82 g of polylysine to step (2) and continue stirring at 450 rpm for 20 min;

[0043] (4) slowly pouring the solution obtained in step (3) into a culture dish and spreading it flat to a thickness of 1 mm, and drying it in an oven at 47° C. to form a hydrogel film;

[0044] (5) The hydrogel film was immersed in 15 mL of water for 10 min to reach swelling equilibrium, thereby obtaining a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel.

[0045] The clean and fresh pigskin was cut into pieces of 2.5 cm×2.5 cm in size and placed in a fixture. 0.4 g of the hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel sample prepared in this example was evenly applied on the surface of the pigskin. A certain force was applied to allow it to react for 60 minutes, and then its bonding strength was tested.

[0046] Example 2

[0047] The rest is the same as in Example 1, except that the stirring time in step (2) is 20 min.

[0048] Example 3

[0049] The rest is the same as in Example 1, except that the stirring time in step (2) is 30 min.

[0050] Comparative Example 1

[0051] A method for preparing a sodium hyaluronate / polylysine hydrogel comprises the following steps:

[0052] (1) dispersing 0.98 g of sodium hyaluronate in 140 mL of ultrapure water, stirring at 45° C. and 450 rpm to fully dissolve the sodium hyaluronate to obtain a sodium hyaluronate aqueous solution;

[0053] (2) Add 1.82 g of polylysine to the sodium hyaluronate aqueous solution and stir at 450 rpm for 20 min;

[0054] (3) slowly pouring the above solution into a culture dish and spreading it flat with a thickness of 1 mm, and drying it in an oven at 47°C to form a hydrogel film;

[0055] (4) The hydrogel film was immersed in 15 mL of water for 10 min to achieve swelling equilibrium, thereby obtaining a sodium hyaluronate / polylysine hydrogel.

[0056] Cut clean and fresh pigskin into 2.5 cm×2.5 cm size and place in a fixture. Take 0.4 g of the sodium hyaluronate / polylysine hydrogel sample prepared in this comparative example and evenly spread it on the surface of the pigskin. Apply a certain force to make it react for 60 minutes and then test its bonding strength.

[0057] Test Case

[0058] The adhesion strength, water absorption and retention properties, and in vitro degradation ability of the hydrogels obtained in the above-mentioned Comparative Example 1 (a: HA / EPL), Example 1 (b: HA / H2O2 / EPL 10 min), Example 2 (c: HA / H2O2 / EPL 20 min), and Example 3 (d: HA / H2O2 / EPL 30 min) were tested, and the hydrogels in each example and comparative example were tested for methyl orange release and antibacterial properties. The results are shown below.

[0059] 1. Infrared detection

[0060] The sodium hyaluronate / polylysine hydrogel (HA / EPL) prepared in Comparative Example 1 and the hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel (HA / H2O2 / EPL) prepared in Example 1 were detected by FT-IR. Figure 1 As shown. 3300-3000cm in the infrared image -1 The infrared peaks appearing at are related to the stretching vibration of NH and the vibration of the carbonyl group in the amide. From the comparison of the infrared curves a and b in the figure, it can be seen that after the addition of hydrogen peroxide, more aldehyde groups participate in the reaction to form amide bonds. At this time, the surrounding environment of the amide bond changes, forming intramolecular or intermolecular hydrogen bonds, etc. Compared with curve a, the vibration frequency of NH in curve b has changed significantly. 1640-1600cm -1 The main absorption peak is the stretching vibration of the carbon-carbon double bond. Since hydrogen peroxide is oxidizing, it can break the CH bond of the hydroxyl group and introduce oxygen atoms to form an aldehyde group. The new absorption peak for the stretching vibration of the OHA aldehyde group (-CHO) appears at 1730cm -1 The primary hydroxyl group (terminal hydroxyl group) on the sodium hyaluronate molecular chain is more easily oxidized than the secondary hydroxyl group. The oxidation reaction process may involve the generation of hydroxyl radicals. These free radicals react with hydroxyl groups to gradually convert hydroxyl groups into carbonyl groups. If carbonyl compounds form hydrogen bonds with compounds containing active hydrogen (such as hydroxyl groups, amino groups, etc.), the stretching vibration frequency of the carbonyl group will also decrease. The formation of hydrogen bonds changes the electron cloud distribution of the carbonyl group, reducing its bond force constant.

[0061] 2. Adhesion strength performance test

[0062] The hydrogel films obtained in Comparative Example 1, Example 1, Example 2, and Example 3 were tested for adhesion strength using a texture analyzer. The sample preparation process and test method were based on ASTM F2258-05 (2015). The mass of the hydrogel film sample was controlled at 0.4 g. The measurement range was 5000 cN, the preload was 10 cN, and the stretching rate was 2 mm / min. The test results are shown in Figure 1. Figure 2 As shown, the hydrogel prepared in Example 1 has the highest bonding strength, and the bonding strength of the hydrogels prepared in Examples 2 and 3 is comparable. The bonding performance of the sodium hyaluronate / polylysine hydrogel is improved by adding hydrogen peroxide, because the hydrogen peroxide oxidizes the hydroxyl groups in the sodium hyaluronate to generate aldehyde groups or carboxyl groups, and a part of the aldehyde groups after oxidation react with the amino groups in the polylysine to generate a dynamic covalent Schiff base. In addition, a part of the carboxyl groups after oxidation can not only generate hydrogen bonds with the carboxyl groups in the water, but also generate hydrogen bonds with the unreacted amino groups. However, as the oxidation time increases, more carboxyl groups will be generated in the solution, and at this time, the carboxyl groups will be oxidized to high oxidation state groups. This peroxidation reaction will change the acidity and charge properties of sodium hyaluronate, thereby affecting the interaction relationship with other molecules, and at this time, the bonding strength of the hydrogel will be reduced. The formation of two chemical bonds contributes to the improvement of the viscosity of the hydrogel after hydrogen peroxide oxidation. It can be seen that hydrogen peroxide provides more oxidized groups in the whole reaction, which increases the bonding strength of the hydrogel.

[0063] 3. Water absorption and retention test

[0064] The sample was cut into 1 cm × 1 cm cubes, dried at 45 °C to constant weight (M0), then immersed in distilled water for 60 min and suspended for 60 s to remove free water on the surface. The weight at this time was M0. 60 , the weight is M 60 The hydrogel was placed in a tube equipped with a filter, centrifuged at 3500 rpm / min for 3 min, and the weight was weighed as Md.

[0065]

[0066] In the formula, M0, M 60 、M d The units are consistent.

[0067] The results are as follows Figure 3As shown, when sodium hyaluronate is oxidized by hydrogen peroxide, compared with sodium hyaluronate / polylysine hydrogel, the structure of sodium hyaluronate is changed by hydrogen peroxide, making the network structure more densely cross-linked and the hydrogel structure more cross-linked. The water absorption in Experimental Example 1 is lower than that in other experimental groups, while the water retention rate is the opposite, which is determined by the hydrogen bonds and van der Waals forces between water molecules and hydrophilic groups in the hydrogel. In addition, the enhanced cross-linking delays the evaporation of absorbed water molecules, thereby improving water retention.

[0068] 4. Antibacterial performance test

[0069] The antibacterial effect of the hydrogel films obtained in Comparative Example 1, Example 1, Example 2, and Example 3 was detected by diffusion method. First, the hydrogel films obtained in Comparative Example 1, Example 1, Example 2, and Example 3 were made into samples of equal mass and area. Escherichia coli and Staphylococcus aureus were cultured overnight to the logarithmic growth phase for use. Escherichia coli and Staphylococcus aureus without sample addition were used as negative controls, and the agar plate with sample addition was used as positive control, and was placed in a 37°C incubator for 12 hours. The antibacterial ability was determined by measuring the size of its inhibition zone.

[0070] like Figure 4 As shown, the sodium hyaluronate / polylysine hydrogel that has not been oxidized with hydrogen peroxide can destroy the membrane structure of Staphylococcus aureus and Escherichia coli to a certain extent due to the antibacterial effect of polylysine. After sodium hyaluronate is modified by hydrogen peroxide, the degree of destruction of the cell membranes of the two bacteria is significantly improved, and the cell membranes of all bacteria are almost severely damaged. The sodium hyaluronate / polylysine hydrogel oxidized with hydrogen peroxide for 10 minutes has a lower antibacterial performance than Example 2 and Example 3 due to the shorter oxidation time, but still has a certain antibacterial ability.

[0071] 5. In vitro degradation performance test

[0072] The hydrogels obtained in Comparative Example 1, Example 1, Example 2, and Example 3 were subjected to an in vitro degradation experiment. The obtained hydrogels were cut into 1 cm × 1 cm squares, weighed as M0, and then placed in a pH 7.4 PBS buffer and placed in a 37°C constant temperature and humidity incubator. They were taken out after 1 day, 3 days, and 9 days of degradation, respectively, and weighed as M1 after drying. The degradation rate was calculated according to the formula:

[0073] In the formula, the units of M0 and M1 are consistent.

[0074] Results from Figure 5As shown, in Examples 1, 2, and 3, due to the oxidation of sodium hyaluronate by hydrogen peroxide, more aldehyde groups are generated to react with amino groups to form amide bonds, and amide bonds are easily hydrolyzed in the water environment of PBS, and water molecules attack chemical bonds to break the bonds, causing the polymer molecular chains to gradually decompose into smaller fragments, destroying the structure of the hydrogel, resulting in more degradation compared with Comparative Example 1.

[0075] 6. Methyl Orange Release Detection

[0076] The hydrogels obtained in Comparative Example 1, Example 1, Example 2, and Example 3 were loaded with methyl orange, and the loading was performed at 24 h, the time point with the highest loading rate. The water on the surface of the loaded hydrogel was wiped dry, and the hydrogel was placed in 5 mL of PBS buffer with a pH of 7.4, and released at a temperature of 37° C. and 100 rpm. At different time points, 2 mL of the dilution was taken, and an equal amount of buffer was added. The absorbance of the dilution was measured using an ultraviolet spectrophotometer, and the cumulative release amount was calculated according to the formula:

[0077]

[0078] Among them, C i and C n is the concentration of MO in the solution at this time, in mg / mL; V i is the volume of buffer taken out each time, which is 200 μL; V is the total volume of buffer, which is 5 mL; W is the MO content loaded in the hydrogel, in mg / mL.

[0079] like Figure 6 As shown, under neutral conditions, with Comparative Example 1 as a control, methyl orange (MO) was used as a negatively charged drug model to evaluate its drug release ability. Larger porosity and network structure can load and release more MO. Compared with Comparative Example 1, Example 1 has a higher ability to release MO. And the first 6 hours is the rapid release period of the hydrogel, which can reflect the strength of the interaction between the hydrogel and MO and the tightness of the hydrogel structure to MO.

[0080] The detailed description of a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel and its preparation method with reference to the above-mentioned examples is illustrative rather than restrictive, and several examples can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel, characterized in that: The preparation method comprises the following steps: (1) heating sodium hyaluronate in ultrapure water until it is completely dissolved to obtain a sodium hyaluronate aqueous solution; (2) slowly adding hydrogen peroxide solution to the sodium hyaluronate aqueous solution, and continuing to stir for 10 to 30 minutes after the addition is completed; (3) adding polylysine powder to the mixed solution obtained in step (2) and continuing stirring for 20 to 30 minutes; (4) spreading the reaction solution obtained in step (3) and drying it at 40 to 60° C. to obtain a hydrogel film; (5) Soaking the hydrogel film in ultrapure water until swelling equilibrium is achieved to obtain a hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel.

2. The preparation method according to claim 1, characterized in that: In step (1), the heating temperature is 40-60°C.

3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the sodium hyaluronate aqueous solution is 5 to 10 g / L.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the sodium hyaluronate to polylysine is 1:1.0-4.

0.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the sodium hyaluronate to hydrogen peroxide is 1:0.018-0.

04.

6. The preparation method according to claim 1, characterized in that: In step (2), the mass concentration of the hydrogen peroxide solution is 20-30%.

7. The preparation method according to claim 1, characterized in that: In step (2), the dropping speed of the hydrogen peroxide solution is 35 to 45 mL / h.

8. The preparation method according to claim 1, characterized in that: In step (5), the mass volume ratio of the hydrogel film to ultrapure water is 1 mg: 2-10 mL.

9. The hydrogen peroxide-modified sodium hyaluronate / polylysine hydrogel prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Cross-linked sodium hyaluronate gel for injection and preparation method thereof

    CN118027454A